Domestication And Foreignization In The Subtitle Translation Of David Attenborough: A Life On Our Planet - Siti Hardiana; Nurma Dhona Handayani (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study investigates domestication and foreignization strategies in the Indonesian subtitle translation of David Attenborough A Life on Our Planet. The research focuses on how subtitle translation mediates environmental discourse cultural representation and audience comprehension. A qualitative descriptive approach was employed to analyze selected subtitle units containing ecological terminology cultural references and evaluative expressions. The findings reveal that domestication is the dominant translation strategy applied to enhance readability and viewer accessibility. Foreignization appears selectively to preserve scientific accuracy institutional identity and documentary credibility. The strategic distribution demonstrates conscious mediation between simplification and precision in documentary subtitling. This study contributes to audiovisual translation research by highlighting the role of subtitle strategies in shaping environmental knowledge transmission and intercultural communication.